Social media and social life: A cross study on university students in Istanbul and Rome - Can, Zeynep Bilgehan (My University, 2018)
This study has been designed to explore the changes in social life of university students both online and in daily life due to the developments and wide usage of social media. Moreover, it was particularly chosen to be a comparative case study to examine whether the context affects these changes and to make the study more comprehensive. The study focused on issues such as relationships and communication with family, friends (close, far, romantic) and formal contacts on social media, privacy, the sharing culture and changes in daily life due to using social media. The study aims to contribute to the understanding of social change and transformation especially in social life brought about by using social media. The study was conducted as a comparative case study in which students from different departments of various public and private universities in Istanbul and Rome took part. Participants were chosen from undergraduate and graduate students who were between the ages of twenty to thirty and active users on at least one social media platform or application. Data were collected through semi-structured interviews with students. The findings of the study indicated that social media has different effects on various kind of relationships. Sharing is seen as a habitual, automatic, collective action. Sharing is believed to have evolved into ‘showing’ and serves different purposes. Tough they may be ground for serious debates and news, social media platforms are also spaces to have fun and to hang out. One important function of social media is the fact that it works like an archive which is easy to reach for users. Its positive and negative effects on daily life are observed to be almost equal. Privacy is still important, however, for certain platforms or content publicity can be preferred. The results in the two cases of the study were found to be very similar, there were only a small number of minor differences.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Social media; Social life; Communication; Privacy; Sharing; İstanbul; Rome; Sosyal medya; Sosyal hayat; İletişim; Mahremiyet; Paylaşım